2021
DOI: 10.3390/su13179620
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Green Infrastructure Location Based on a Social Well-Being Index

Abstract: Urban Green Infrastructure (GI) provides promising opportunities to address today’s pressing issues in cities, mainly resulting from uncurbed urbanization. GI has the potential to make significant contributions to make cities more sustainable by satisfying the growing appetite for higher standards of living as well as helping cities adapt to extreme climate events. To leverage the potentials of GI, this article aims to investigate the effectiveness of GI that can enhance social welfare benefits in the triple-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…To date, the analyses of UGI reported by several authors [22][23][24][25][26] revealed that UGIs have multiple benefits, such as recreation, improving physical and mental health, and regulating services. However, less reports have been found on the reduction of unemployment and economic benefits of UGI that serve as a smokeless industry (urban tourism), which has a significant role in poverty alleviation of developing countries, such as Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the analyses of UGI reported by several authors [22][23][24][25][26] revealed that UGIs have multiple benefits, such as recreation, improving physical and mental health, and regulating services. However, less reports have been found on the reduction of unemployment and economic benefits of UGI that serve as a smokeless industry (urban tourism), which has a significant role in poverty alleviation of developing countries, such as Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…However, less reports have been found on the reduction of unemployment and economic benefits of UGI that serve as a smokeless industry (urban tourism), which has a significant role in poverty alleviation of developing countries, such as Ethiopia. In addition, many UGIs lack appropriate planning and urban infrastructure networks, and do not focus on preventing human induced climate changes and lately emerged social health concerns, such as the COVID-19 pandemic [23][24][25][26]. Out of 171 reports on UGI, the vast majority of the research was from the United States, Australia, and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, perceived lack of exposure to green space has been independently linked with overweight in the youths [2] and mental and physical health issues [16]. Following this, the United Nations General Assembly (2016) noted that the provision and usage of green spaces are integral parts of the Habitat III Agenda aimed at promoting human health and well-being in urban areas in the 21st Century and contributing to the attainment of the sustainable development goals [17] This provision of green open spaces will reduce the effect of global climate change which has been projected to cause changes in climate parameters and directly affect organism on earth [18].…”
Section: Introductionmentioning
confidence: 99%